PRAGMATIC FEATURES OF VERB TYPES IN ENGLISH AND UZBEK LANGUAGES: ENGLISH AND UZBEK LITERARY WORKS AS EXAMPLES - Hulkar Mingbayeva G’afforovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This thesis investigates the pragmatic features of verb types in English and Uzbek languages by delving into the structural and functional aspects of verbs in both linguistic systems. Through a comparative analysis of verb types in English and Uzbek literary works, the study aims to elucidate how cultural contexts and language-specific characteristics influence the pragmatic functions of verbs in communication.